Design, synthesis, and biological evaluation of amide derivatives of imidazo[2, 1-b][1, 3, 4]thiadiazole as anticancer agents. Issue 21 (1st November 2020) - Sridhar, Gattu; Palle, Sadanandam; Vantikommu, Jyothi; Gangarapu, Kiran
Abstract: A new library of amide derivatives of imidazo[2, 1- b ][1, 3, 4]thiadiazoles (11a–j ) have designed and synthesized and their structures determined by 1 H NMR, 13 C NMR, mass and HRMS spectral data. Further, all these compounds were evaluated for their anticancer potentials on a panel of cancer cell lines like MCF-7, MDA MB-231 (breast carcinoma), A549 (lung carcinoma) and DU-145 (prostate carcinoma) by using MTT assay and obtained IC50 values were compared with well-known chemotherapeutic agent etoposide. Among them, compounds 11b–e and 11i showed potent anticancer activity against the entire cancer cell lines than the chemotherapeutic drug. Particularly, one compound 11b demonstrated prominent activity. Graphical Abstract: